Analysis Of The Dimensions Of Intellectual Capital In Commercial Banks Using SWOT Tool (Afield Study In Commercial Banks In The Syrian Coast) (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The research aimed to determine the role of (SWOT) tool in analyzing of intellectual capital in the branches of commercial banks in the Syrian coast. and determining the most  important factors that could influence the intellectual capital within the banks under study, The strength and support of intellectual capital and weaknesses in intellectual capital and ways to address them, and the most important factors that will help commercial banks in identifying the most important opportunities for the development of intellectual capital and the most important threats that may face it, the research relied on the deductive approach, in order to characterize variables The Urged and analysis based on preliminary data collected, in addition to secondary data available, through a questionnaire developed by informed researcher on the published literature, and has been relying on statistical analysis software (SPSS), as a tool for the analysis of the available data. The research concluded: 1-There is a significant relationship between the use of SWOT tool in the analysis of human capital of relative importance (69.152%), in the analysis of structural capital and of relative importance (78.384%), in the analysis of client capital and of relative importance (77.288%) in Syrian commercial banks studied. 2-There is a significant relationship between the use of the tool (SWOT) in the analysis of intellectual capital in the Syrian commercial banks studied. 3-Syrian commercial banks have the human resources and the great physical possibilities to use SWOT tool in analyzing intellectual capital and drawing banking strategies in the banking market. هدف البحث إلى تحديد دور أداة (SWOT) في تحليل رأس المال الفكري في فروع المصارف التجارية في الساحل السوري، وتحديد أهم العوامل التي من شانها التأثير على رأس المال الفكري داخل المصارف محل الدراسة، وتحديد مجموعة من العوامل التي من شأنها مساعدة المصارف التجارية في تحديد أهم نقاط قوة رأس المال الفكري وتدعيمها ونقاط الضعف في رأس المال الفكري وسبل معالجتها، وأهم العوامل التي من شانها مساعدة المصارف التجارية في تحديد أهم فرص تطوير رأس مالها الفكري واهم التهديدات التي من الممكن أن تواجه ذلك، واعتمد البحث على المقاربة الاستنباطية، وذلك من أجل توصيف متغيرات البحث وتحليلها اعتماداً على البيانات الأولية التي تم جمعها، بالإضافة إلى البيانات الثانوية المتوفرة، من خلال استبانة تم تطويرها من خلال اطلاع الباحث على الأدبيات المنشورة ثم تم الاعتماد على برنامج التحليل الإحصائي (SPSS)، كأداة لتحليل البيانات المتوفرة. وتوصل البحث إلى أن: 1-هناك علاقة معنوية بين استخدام أداة (SWOT) في تحليل رأس المال البشري بأهمية نسبية بلغت (69.152%)، وفي تحليل رأس المال الهيكلي وبأهمية نسبية بلغت (78.384%)، وفي تحليل رأس المال الزبائني وبأهمية نسبية بلغت (77.288%) في المصارف التجارية السورية المدروسة. 2-هناك علاقة معنوية بين استخدام أداة (SWOT) في تحليل رأس المال الفكري في المصارف التجارية  السورية المدروسة. 3-تمتلك المصارف التجارية السورية الموارد البشرية والإمكانيات المادية الكبيرة لاستخدام أداة (SWOT) في تحليل رأس المال الفكري ورسم الاستراتيجيات المصرفية في السوق المصرفية.